PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING MENGGUNAKAN LIVEWORKSHEETS PADA ELEMEN PENGUKURAN PEMBELAJARAN MATEMATIKA DI KELAS IV SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to produce a valid, practical, and effective e-LKPD product based on problem-based learning using live worksheets on the measurement elements of mathematics learning in grade IV of elementary school. The background of this research is the minimal use of technology in the learning process in elementary schools. This research is a type of development research using a Research and Development (R&D) approach. This study uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study were fourth-grade students at SDN 06 Lumindai, SDN 15 Lumindai, and SDN 29 Lumindai. The types of data used in this study are qualitative and quantitative data. The instruments used were interviews, observations, questionnaires, and tests. The results of the study obtained a validity level with a percentage of 94.23% with the category "very valid". Data from the teacher's practicality test showed a category of "very practical" with a percentage of 88.4% and 91.05% in the student's practicality test with the category "very practical". Then the effectiveness test was also carried out by determining the average N-Gain Score from each school which obtained results of 0.75 for meeting I and 0.77 for meeting II so that it is included in the "high" criteria with the "effective" category. Based on the results of the research that has been done it can be concluded that PBL-based e-LKPD using liveworksheets on the measurement elements is valid, practical, and effective for use in learning mathematics for fourth-grade elementary school.